The extracellular matrix as a scaffold for tissue reconstruction - Badylak, S.F.
The extracellular matrix (ECM)consists of a complex mixture of structural and functional proteins and serves an important role in tissue and organ morphogenesis, maintenance of cell and tissue structure and function,and in the host response to injury. Xenogeneic and allogeneic ECM has been used as a bioscaffold for the reconstruction of many different tissue types in both pre-clinical and human clinical studies. Common features of ECM-associated tissue remodeling include extensive angiogenesis,r ecruitment of circulating progenitor cells,rapid scaffold degradation and constructive remodeling of damaged or missing tissues. The ECM-induced remodeling response is a distinctly different phenomenon from that of scar tissue formation.
Keywords: EXTRACELLULAR MATRIX; SMALL INTESTINAL SUBMUCOSA (SIS); BIOSCAFFOLDS; TISSUE ENGINEERING; URINARY BLADDER SUBMUCOSA (UBS)